IMPLEMENTASI PERATURAN WALIKOTA NOMOR 36 TAHUN 2013 TENTANG KEBIJAKAN KOTA LAYAK ANAK - Ratri, Dewi Kartika (Fakultas Ilmu Sosial dan Ilmu Politik, 2014)
Children Friendly City policy is an effort to guarantee the fulfillment of the needs and protection of childrens rights, child care and childrens participation in the construction carried out in collaboration with stakeholders across sectors. Probolinggo became one of the adopts the policy. In contrast to other areas that have been bearing the title of children friendly city as Surabaya, Semarang, Malang and others, Probolinggo currently still holds the status âtowards child-friendly cityâ.This research is a qualitative descriptive study using data collection methods of interview, observation and documentation. The purpose of this research to know the implementation process Probolinggo Mayor Regulation Number 36 of 2013 about children friendly city. During the implementation process doesnât go smoothly there is problem. The issue of communication between policy implementers and implementers alike with the community, then the problem disposition implementing policies is still low, the lack of expertise of the human resources involved in policy and budget issues. Based on the phenomenon that occurs researcher interested in analyzing it using the theories of Edward III of policy implementation that consists of four indicators, namely communication, resources, disposition and bureaucratic structures.Survey results revealed that there was miscommunication between implementers and information is still not up to community because the community doesnât know about the policy. On variable human resources of implementers policies the number has sufficient but for the skill still needs to be improved. Disposition is also a chore that needs to be resolved because commitment of implementers policies is still low. Fulfillment 31 indicators of child-friendly city is determined by the Ministry of Womens Empowerment is also still ongoing. Accordingly, need to increase the intensity of coordination through meetings held every month, and training workshops aiming improving skills and policy implementers make binding rules for implementers policies that are negligent to their duties and obligations.Keywords : Children friendly city, implementation of policies.